Arabic Language Program Students' Difficulties in Memorizing Hadith - Guslianto, Guslianto; Azis, Nurazmi; Burhanuddin, Burhanuddin; Yenti, Erna; Busral, Busral; Hakim, Lukman; Sartika, Rika (Al-kayyis: Journal of Islamic Education, 2023)
Memorizing hadith is an activity that cannot be separated from the routine of Islamic studies students in fulfilling the demands of the course. However, in reality there are still students who have difficulty memorizing hadiths. So research needs to be carried out to find out these difficulties. This research aims to find out how difficult it is for students to memorize Hadith. This research uses a qualitative method with a case study type. Research data was taken through direct interviews with eleven informants consisting of nine female students and two lecturers. All interview data was then analyzed thematically using NVivo 12 Software. Research findings showed seven difficulties for students in memorizing hadith, these seven difficulties are i) Not yet proficient in reading Arabic texts, ii) Not knowing the translation of Hadith, iii) Not understanding the content of Hadith, iv) Not yet used to memorizing Hadith, v) Often feeling lazy, vi) Matan Hadith is too long, vii) Mufradat in gharibah Hadith. The findings in this research have proven that students have difficulty memorizing hadith. The results of this research can be used as a reference for further research in examining this discussion in other contexts.